Incidence Rate of Thyroid Cancer in Wasit Province From (2017–2021) Related with Age and Gender - Zainab Abdalameer Alqurashi (Journal of Biomedicine and Biochemistry, 2023)
Background Thyroid cancer developing when the cells of thyroid gland grow abnormally. The characteristic of thyroid cancer involve swelling or a tumor in the neck. Objective Knowledge the incidence rate of Thyroid cancer in Wasit Province from (2017–2021) related with Age and Gender. Results In our research, cancer data were taken in Wasit Governorate for patients attending the Al-Karama Teaching Hospital for the period From 2017 to 2021, the results showed that thyroid cancer had recorded in- cidence reach (13.004%), where 42 out of 323 cases of cancer were recorded in last five years.The data were distributed according to the years as they were distributed over the years (2017 to 2021), where the highest rate of in- fection was in the year 2020,While the lowest rate of infection was recorded in 2019 with a frequency of 5 cases.As for the relationship of thyroid cancer with gender, the results showed that thyroid cancer had 21.42% of cases in males, while in females had 78.57%.The relationship of the disease with the age was found the majority of the 9 patients in this study were between the ages of 50 and 59, making about 21.4% of the total. Eight instances (19.1%) were found in people aged 40–49, while seven cases (16.7%) were found in people aged 30–39. Two occurrences of thyroid cancer were re- ported in people aged 70 to 79, the age group with the lowest incidence rate. Conclusion Thyroid cancer in the past 5 years showed the highest rate of cases was recorded in 2020. Relationship of the disease with gender has shown that females are more affected than male . Relationship with age factor found that the most vulnerable age groups are 50-59 years old.